2012
DOI: 10.1364/ol.37.000653
|View full text |Cite
|
Sign up to set email alerts
|

Infrared camera based on a curved retina

Abstract: Design of miniature and light cameras requires an optical design breakthrough to achieve good optical performance. Solutions inspired by animals' eyes are the most promising. The curvature of the retina offers several advantages, such as uniform intensity and no field curvature, but this feature is not used. The work presented here is a solution to spherically bend monolithic IR detectors. Compared to state-of-the-art methods, a higher fill factor is obtained and the device fabrication process is not modified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…We demonstrated that the electro-optical performances of a curved infrared 320 x 256 detectors array, based on 25 µm pitch Si-CMOS infrared bolometric structures, were unchanged [14][15]. This result illustrates the fact that the stress induced in the device, evaluated around 150 MPa (max) for a 80 mm concave bending radius, is not sufficient to induce mechanical damages in the micromechanical structure of the device (above-IC suspended membranes).…”
Section: Hemispherical Infrared Focal Plane Arraysmentioning
confidence: 97%
“…We demonstrated that the electro-optical performances of a curved infrared 320 x 256 detectors array, based on 25 µm pitch Si-CMOS infrared bolometric structures, were unchanged [14][15]. This result illustrates the fact that the stress induced in the device, evaluated around 150 MPa (max) for a 80 mm concave bending radius, is not sufficient to induce mechanical damages in the micromechanical structure of the device (above-IC suspended membranes).…”
Section: Hemispherical Infrared Focal Plane Arraysmentioning
confidence: 97%
“…[5][6][7][8][9][10] For example, hemispherical photodetector arrays that mimic the vertebrate eyes have shown superior imaging characteristics with simple optics. [11][12][13][14][15][16][17] Different fabrication strategies have been developed to realize such devices.…”
Section: Introductionmentioning
confidence: 99%
“…Pure mono-and polycrystalline silicon lenses are used intensively in the manufacturing of micro-electromechanical systems. However, silicon has become one of the preferred materials for making optical components such as infrared lenses and optical transmitters [1][2][3]. Silicon is suitable for optical applications with a mid-wave infrared range of 0.3 -0.5 µm.…”
Section: Introductionmentioning
confidence: 99%